Teacher Well-Being and Its Influence on School Effectiveness: A Quantitative Study - Siswanto, Deny Hadi; Hanama, Akhmad; Apriwulan, Hamdani Fajar (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
Teacher well-being is presumed to influence school effectiveness; however, empirical evidence within the Indonesian context remains limited. This quantitative study examines the relationship between teacher well-being and school effectiveness at Muhammadiyah Mlati Senior High School. Data were collected through a structured survey administered to 36 teachers using a Google Forms questionnaire of 20 items—10 related to teacher well-being and 10 to school effectiveness. The data were analyzed using simple linear regression. The findings indicate a statistically significant positive relationship between teacher well-being and school effectiveness (p = 0.033). However, the explanatory power of teacher well-being accounts for only 12.7% of the variance in school effectiveness. These results suggest that while teacher well-being contributes, its impact is relatively modest, highlighting the importance of other influencing variables such as administrative support, organizational climate, and infrastructure availability. The study offers theoretical contributions aligned with Self-Determination Theory and practical implications for policymakers and educational stakeholders, emphasizing the need for comprehensive strategies that integrate teacher welfare, professional development, and managerial improvement to enhance overall educational quality.